ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI INITIAL RETURN PADA PENAWARAN SAHAM PERDANA - Wiguna, I Gd Nandra Hary; Yadnyana, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.12.TAHUN 2015, 2016)
Initial return been gains received by investors in the secondary market because the occurrence of underpricing on the stocks of companies that have an IPO. The aim of this research is to find an initial return of influence. The research  was done in Indonesia Stock Exchange (BEI) in corporations that made IPOs in 2009-2013 periods. The study sample as many as 78 company performed with sampling purposive technique. Multiple regression was used to analyze. The result of multiple regression analysis showed that corporation size and auditor reputation significantly have a negative effect on initial return. While financial leverage significantly has a positive effect on initial return. ROA, EPS, corporation life time, underwriter reputation and industrial sector do not have an effect on initial return. In the light of the result it can be concluded that the determinants of initial return are corporation size, financial leverage, and auditor reputation.
Keywords: IPO, Underpricing, Initial Return